Up-regulation of miR-31 in human atrial fibrillation begets the arrhythmia by depleting dystrophin and neuronal nitric oxide synthase - Reilly, S; Liu, X; Carnicer, R; Recalde, A; Muszkiewicz, A; Jayaram, R; Carena, M; Wijesurendra, R; Stefanini, M; Surdo, N; Lomas, O; Ratnatunga, C; et al. (American Association for the Advancement of Science, 2016)
Atrial fibrillation (AF) is a growing public health burden, and its treatment remains a challenge. AF leads to electrical remodeling of the atria, which in turn promotes AF maintenance and resistance to treatment. Although remodeling has long been a therapeutic target in AF, its causes remain poorly understood. We show that atrial-specific up-regulation of microRNA-31 (miR-31) in goat and human AF depletes neuronal nitric oxide synthase (nNOS) by accelerating mRNA decay and alters nNOS subcellular localization by repressing dystrophin translation. By shortening action potential duration and abolishing rate-dependent adaptation of the action potential duration, miR-31 overexpression and/or disruption of nNOS signaling recapitulates features of AF-induced remodeling and significantly increases AF inducibility in mice in vivo. By contrast, silencing miR-31 in atrial myocytes from patients with AF restores dystrophin and nNOS and normalizes action potential duration and its rate dependency. These findings identify atrial-specific up-regulation of miR-31 in human AF as a key mechanism causing atrial dystrophin and nNOS depletion, which in turn contributes to the atrial phenotype begetting this arrhythmia. miR-31 may therefore represent a potential therapeutic target in AF.